Transgenerational exposure to ocean acidification impacts the hepatic transcriptome of European sea bass (Dicentrarchus labrax) - Pauline Auffret; Arianna Servili; Anne-Alicia Gonzalez; Marie-Lou Fleury; Felix Christopher Mark; David Mazurais (BMC Genomics, 2023)
Abstract Physiological effects of ocean acidification associated with elevated CO2 concentrations in seawater is the subject of numerous studies in teleost fish. While the short time within-generation impact of ocean acidification (OA) on acid-base exchange and energy metabolism is relatively well described, the effects associated with transgenerational exposure to OA are much less known. Yet, the impacts of OA can vary in time with the potential for acclimation or adaptation of a species. Previous studies in our lab demonstrated that transgenerational exposure to OA had extensive effects on the transcriptome of the olfactory epithelium of European sea bass (Dicentrarchus labrax), especially on genes related to ion balance, energy metabolism, immune system, synaptic plasticity, neuron excitability and wiring. In the present study, we complete the previous work by investigating the effect of transgenerational exposure to OA on the hepatic transcriptome of European sea bass. Differential gene expression analysis was performed by RNAseq technology on RNA extracted from the liver of two groups of 18 months F2 juveniles that had been exposed since spawning to the same AO conditions as their parents (F1) to either actual pH or end-of-century predicted pH levels (IPCC RCP8.5), respectively. Here we show that transgenerational exposure to OA significantly impacts the expression of 236 hepatic transcripts including genes mainly involved in inflammatory/immune responses but also in carbohydrate metabolism and cellular homeostasis. Even if this transcriptomic impact is relatively limited compared to what was shown in the olfactory system, this work confirmed that fish transgenerationally exposed to OA exhibit molecular regulation of processes related to metabolism and inflammation. Also, our data expand the up-regulation of a key gene involved in different physiological pathways including calcium homeostasis (i.e. pthr1), which we already observed in the olfactory epithelium, to the liver. Even if our experimental design does not allow to discriminate direct within F2 generation effects from transgenerational plasticity, these results offer the perspective of more functional analyses to determine the potential physiological impact of OA exposure on fish physiology with ecological relevance.